Prion Diseases - Baker, Harry F.; Ridley, Rosalind M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1996)
In Prion Diseases leading researchers and clinicians describe their state-of-the-art findings and hypotheses arising from a variety of different approaches to this group of diseases. Their approaches include clinical presentations, epidemiology, transgenic methods, and diagnostic tests via transmission electron microscopy and immunoblotting. The diseases covered include human and animal spongiform encephalopathies, such as Creutzfeldt-Jakob disease, mad cow disease, and scrapie. Prion Diseases illuminates the conflicting hypotheses that have evolved to explain these diverse disorders which can appear as infectious diseases a genetically determined diseases, as well as ones sharing neuropathological similarities with such common neurodegenerative diseases as Alzheimer's disease, Parkinson's disease, and amyotropic lateral sclerosis. It provides a much-needed overview of various approaches to understanding these diseases by showing how researchers have analyzed their different facets, ranging from the epidemiology of the human versions to molecular genetics of the animal forms of the diseases.
The Paradox of Prion Disease -- Human Spongiform Encephalopathy -- Neuropathological Diagnosis of Human Prion Disease -- Neuropathological Diagnosis of Human Prion Disease -- The Diagnosis of Bovine Spongiform Encephalopathy and Scrapie by the Detection of Fibrils and the Abnormal Protein lsoform -- Exposure to, and Inactivation of, the Unconventional Agents that Cause Transmissible Degenerative Encephalopathies -- Surveillance of Prion Diseases in Humans -- Environmental Causes of Human Spongiform Encephalopathy -- Bovine Spongiform Encephalopathy -- Handling the BSE Epidemic in Great Britain -- Special Problems of Genetic Counseling in Adult-Onset Diseases -- Genotyping and Susceptibility of Sheep to Scrapie -- Strain Typing Studies of Scrapie and BSE -- PrP-Deficient Mice in the Study of Transmissible Spongiform Encephalopathies -- Transgenic Approaches to Prion “Species-Barrier” Effects -- Methods for Studying Prion Protein Amyloid -- Methods for Studying Prion Protein (PrP) Metabolism and the Formation of Protease-Resistant PrP in Cell Culture and Cell-Free Systems -- Immunohistochemistry of Resinated Tissues for Light and Electron Microscopy.
Keywords: Cell biology; Cell Biology